Devotee or fan: the town of Orizaba, 1762-1834 (Tzintzun, Revista de Estudios Históricos, 2016)
Throughout the 18th century the town of Orizaba was building an image of devotecity. Image derived from the dense fabric of religious corporations that characterizedits urban space, was also one of the reasons for pride of local patriotism, anargument in the dispute of civil corporations, and local demands to the Crown.However, the piety and devotion from the people of Orizaba were questioned inthe press in early 19th century, forcing the local elite to build a new image of thevillage, related to the promotion of the lights, both culturally and in the renewal ofthe urban space. However, the politicization of first federalism brought criticismsback, increasingly stronger to the village of Orizaba, earlier praised by devoteeand now despised by “fanatical”. This process clearly illustrates how the positionof religion was transforming into public opinion and pathways that secularizationwas building.
Keywords: devotees; fanaticism; public opinion; secularization; Orizaba